A Secure and Scalable Sidechain Model for Fog Computing in Healthcare Systems - Haraty, Ramzi A.; Amhaz, Ali (Informatica, 2025)
With the enormous amount of data produced daily, cloud and fog computing presented efficient and effective models for real-time data exchange. Nevertheless, this technology came with a cost at the security level, where it became an easy target for malicious actions that could quickly spread throughout the model. Blockchain, a recent and promising technology, has shown to be a suitable solution for securing transactions in the fog environment because of the distributed ledger structure that makes it resistant to many types of attacks. Scalability, however, introduced the main drawback of a blockchain by making it inefficient in some real-world applications, especially in the medical field, which includes a lot of data exchange. This work will suggest a scalable and secure model for fog and cloud computing in healthcare systems that depend on sidechains and the clustering of the available fog nodes. The importance of the model is highlighted, and experimental results showed promising outcomes.